An Arabidopsis Mitochondrial Uncoupling Protein Confers Tolerance to Drought and Salt Stress in Transgenic Tobacco Plants - Begcy, Kevin; Mariano, Eduardo D.; Mattiello, Lucia; Nunes, Alessandra V. [UNESP]; Mazzafera, Paulo; Maia, Ivan de Godoy [UNESP]; Menossi, Marcelo (Public Library Science, 2011)
Background: Plants are challenged by a large number of environmental stresses that reduce productivity and even cause death. Both chloroplasts and mitochondria produce reactive oxygen species under normal conditions; however, stress causes an imbalance in these species that leads to deviations from normal cellular conditions and a variety of toxic effects. Mitochondria have uncoupling proteins (UCPs) that uncouple electron transport from ATP synthesis. There is evidence that UCPs play a role in alleviating stress caused by reactive oxygen species overproduction. However, direct evidence that UCPs protect plants from abiotic stress is lacking.Methodology/Principal Findings: Tolerances to salt and water deficit were analyzed in transgenic tobacco plants that overexpress a UCP (AtUCP1) from Arabidopsis thaliana. Seeds of AtUCP1 transgenic lines germinated faster, and adult plants showed better responses to drought and salt stress than wild-type (WT) plants. These phenotypes correlated with increased water retention and higher gas exchange parameters in transgenic plants that overexpress AtUCP1. WT plants exhibited increased respiration under stress, while transgenic plants were only slightly affected. Furthermore, the transgenic plants showed reduced accumulation of hydrogen peroxide in stressed leaves compared with WT plants.Conclusions/Significance: Higher levels of AtUCP1 improved tolerance to multiple abiotic stresses, and this protection was correlated with lower oxidative stress. Our data support previous assumptions that UCPs reduce the imbalance of reactive oxygen species. Our data also suggest that UCPs may play a role in stomatal closure, which agrees with other evidence of a direct relationship between these proteins and photosynthesis. Manipulation of the UCP protein expression in mitochondria is a new avenue for crop improvement and may lead to crops with greater tolerance for challenging environmental conditions.